2012
DOI: 10.1111/j.1399-0012.2012.01651.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical rationalization of living donor liver transplantation by abolition of hepatic artery reconstruction under a fixed microscope

Abstract: The small diameter of the hepatic artery is one of the complexities of living donor liver transplantation (LDLT). We analyzed whether the direct suture technique using surgical loupes can simplify the operative process for LDLT compared with fixed microscopic reconstruction. We applied the direct technique to rationalize the operative process and abolished routine microsurgery from 2004. Two hundred and nine LDLT with a postoperative period over 34 months were carried out from 1996 to 2008. The patients were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“… 62 - 64 Operating microscope has been used successfully 65 for complex arterial reconstruction in addition to loupe magnification. 66 , 67 Duct-to-duct anastomosis is currently the preferred technique for biliary reconstruction 54 , 68 except in cases when the recipient bile duct is not healthy. It is controversial whether the use of an external or internal biliary stent can reduce biliary complications, as the stent itself may result in complications.…”
Section: Preamble and Methodsmentioning
confidence: 99%
“… 62 - 64 Operating microscope has been used successfully 65 for complex arterial reconstruction in addition to loupe magnification. 66 , 67 Duct-to-duct anastomosis is currently the preferred technique for biliary reconstruction 54 , 68 except in cases when the recipient bile duct is not healthy. It is controversial whether the use of an external or internal biliary stent can reduce biliary complications, as the stent itself may result in complications.…”
Section: Preamble and Methodsmentioning
confidence: 99%
“…Transplant and HPB surgeons are not very well versed in working under a microscope and additional specialized microsurgical training s required for them to reliably perform the anastomosis confidently (36). The operating microscope provides the benefit of a sound evaluation of donor and recipient vessels to search for and eliminate dissection of the intima, flaps or soft thrombi which Alternatively, there is now growing evidence that suggests reconstruction under loupe provides equitable outcomes with the added benefit of convenience and ease of use as compared to the logistical difficulties associated with a microscope (31,37).…”
Section: Advancements In Arterial Advancements In Arterial Reconstruction Reconstructionmentioning
confidence: 99%
“…Besides the use of microscope for arterial reconstruction, recent literature have shown that the use of surgical loupes for arterial reconstruction have comparable outcomes as microscope with the added advantage of reduction of operation time and some centers also showed reduction in blood loss and hospital stay. [ 59 62 ] This could possibly be attributed to advanced in surgical techniques and improve learning curve gained from years of transplant experience in these centers.…”
Section: Intraoperative Techniquesmentioning
confidence: 99%